High perpendicular coercive field of CoFe2O4 thin films deposited by PLD - Terzzoli, M. C. (2004)
Thin films of CoFe2O4 were deposited on (1 0 0) Si and (1 0 0) MgO substrates by pulsed laser deposition (PLD). The X-ray analysis shows the existence of single-phase spinel structure. Thin films deposited on (1 0 0) MgO substrates are epitaxial and completely oriented in-plane and out of plane due to the small lattice mismatch between Co ferrite and MgO. The surface microstructure was probed by atomic force microscopy and we can describe it like a tidy mosaic of monocrystals. Surprisingly, the films grew on (1 0 0) Si using 355 nm, reveal a complete (1 1 1) orientation in spite of the native oxide of the substrate when deposited. The films deposited with 266 nm also were textured in the (1 1 1) but with less particulate on the surface. (1 0 0) films show at 35 K a perpendicular coercive field Hc as high as 12.9 kOe, meanwhile for the (1 1 1) films Hc was around 9 kOe. However, at room temperature, the (1 1 1) films deposited with 266 nm show a perpendicular coercive field of 5.1 kOe and a squareness of 0.86 which make them attractive for magneto-optic recording applications.e2O4 were deposited on (1 0 0) Si and (1 0 0) MgO substrates by pulsed laser deposition (PLD). The X-ray analysis shows the existence of single-phase spinel structure. Thin films deposited on (1 0 0) MgO substrates are epitaxial and completely oriented in-plane and out of plane due to the small lattice mismatch between Co ferrite and MgO. The surface microstructure was probed by atomic force microscopy and we can describe it like a tidy mosaic of monocrystals. Surprisingly, the films grew on (1 0 0) Si using 355 nm, reveal a complete (1 1 1) orientation in spite of the native oxide of the substrate when deposited. The films deposited with 266 nm also were textured in the (1 1 1) but with less particulate on the surface. (1 0 0) films show at 35 K a perpendicular coercive field Hc as high as 12.9 kOe, meanwhile for the (1 1 1) films Hc was around 9 kOe. However, at room temperature, the (1 1 1) films deposited with 266 nm show a perpendicular coercive field of 5.1 kOe and a squareness of 0.86 which make them attractive for magneto-optic recording applications.